Health Insurance and Access to Care among Social Security Disability Insurance Beneficiaries during the Medicare Waiting Period - Gerald F. Riley (SAGE Publishing, 2006)
For most Social Security Disability Insurance (SSDI) beneficiaries, Medicare entitlement begins 24 months after the date of SSDI entitlement. Many may experience poor access to health care during the 24-month waiting period because of a lack of insurance. National Health Interview Survey data for the period 1994-1996 were linked to Social Security and Medicare administrative records to examine health insurance status and access to care during the Medicare waiting period. Twenty-six percent of SSDI beneficiaries reported having no health insurance, with the uninsured reporting many more problems with access to care than insured individuals. Access to health insurance is especially important for people during the waiting period because of their low incomes, poor health, and weak ties to the workforce.